The Effect of Service Quality, Price Perception and Trust on Parents Satisfaction at Kartika Mandala Kindergarten in Denpasar - Arigata, I Made Dipa; Anggraini, Ni Putu Nita; Ribek, Pande Ketut (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
Kindergarten as an educational institution that develops early childhood skills, must pay attention to the satisfaction of parents who send their children to Kartika Mandala Kindergarten. Because parents' satisfaction with the results of education in kindergarten as a provider of educational services will later determine the number of new student admissions. The purpose of this study is to examine and attain the effect of service quality, price perception, and trust on the satisfaction of parents of students at Kartika Mandala Kindergarten Denpasar. The population in this study was parents of students at Kartika Mandala Kindergarten in the last 5 years, from 2016 to 2020 a total of 277 students. The sampling technique used proportionate stratified random sampling so that 56 people were used as samples. The researchers used multiple linear analysis, classical assumption test, t-test, and F test. Later, it is found that service quality, price perception, and trust positively and significantly affect the satisfaction of parents of students at Kartika Mandala Kindergarten Denpasar. It is recommended to Kartika Mandala Kindergarten Denpasar to further improve the handling of complaints from parents of students, which can be used as input and suggestions to realize better services in the future.